The Development of LearnPro: A Mobile App That Makes Learning More Effective and Enjoyable - Ching Kai Yuan,; DARMAN, ROZANAWATI (Applied Information Technology And Computer Science, 2024)
LearnPro revolutionizes personalized learning with an object-oriented approach within the Flutter framework, ensuring a seamless educational experience. Using Firebase technologies like Firestore for database management and Firebase Authentication for secure access, LearnPro guarantees both functionality and data integrity. It empowers users with user-generated study plans and the Pomodoro timer technique to optimize productivity and focus. The user-defined Roulette Reward Mechanism adds gamification, enhancing motivation. The Analytics module, which graphs focus time, provides insights into study habits, enabling users to improve their strategies. The Notification and Reminder module keeps users organized with timely notifications for upcoming tasks and study sessions. By integrating these features, LearnPro creates a user-friendly and adaptive learning environment, empowering self-directed learners and students to take control of their educational journeys and achieve their goals.